Modelling, Test and Practice of Steel Structures (2022)
This reprint provides an international forum for the presentation and discussion of the latest developments in structural-steel research and its applications. The topics of this reprint include the modelling, testing and practice of steel structures and steel-based composite structures. A total of 17 high-quality, original papers dealing with all aspects of steel-structures research, including modelling, testing, and construction research on material properties, components, assemblages, connection, and structural behaviors, are included for publication.